Investigating the Role of Sodium-Glucose Cotransporter 2 Modulation in Metabolic Syndrome Induced-Chronic Kidney Disease Mouse Model - Cheff, Véronique (Université d'Ottawa / University of Ottawa, 2021)
Chronic kidney disease (CKD) is a worldwide health burden with increases risk of end-stage renal function if left untreated. CKD induced in the context of metabolic syndrome (MS) increases risks of hypertension, hyperglycemia, excess body fat and dyslipidemia. Our Centre previously generated a renin-dependent hypertensive/ type 1 diabetic mouse model and lead to the development of several signs associated with human diabetic kidney disease (DKD), however the extent and impact of dyslipidemia in this model remains unknown. We hypothesized that combining a high-fat diet (HFD) regimen onto the hypertensive/ diabetic phenotype would mimic features of MS induced-CKD in mice. An 8-week-old male genetically hypertensive mice (Lin+) were subjected to streptozotocin (STZ) intraperitoneal (i.p.) injections (50 mg/kg, 5 days consecutive) to induce hyperglycemia. Four-weeks later hypertensive/ diabetic mice (Lin+ mouse with induced beta cells death, also known as LinSTZ) were fed a 60% kCal HFD for 8 weeks. This study shows that HFD-fed LinSTZ mice developed less glomerular hypertrophy, scarring and albuminuria and hepatocytes fat accumulation at endpoint than regular-diet fed littermates. Moreover, antidiabetic drug Canagliflozin, dosed at 30 mg/kg body weight, showed reno-protection in the LinSTZ mice model. Taken together, our results show that LinSTZ mice fed a HFD did not lead to a more robust model of MS induced CKD. In fact, several indices of renal injury were reduced by feeding LinSTZ mice a HFD or treating them with Canagliflozin.
Keywords: Chronic kidney disease; Metabolic syndrome; Diabetes; Hypertension; Obesity; Mouse model; Canagliflozin